KOREAN BABY BOOMERS' INTERNET USE: BEING SOCIALLY ENGAGED OR FEELING ISOLATED?. (11th November 2018) - Kim, J; Bae, Y; Han, G
Abstract: Introduction. Korean baby boomers - born between 1955 and 1963 - are better educated and wealthier than the past generations, but relatively younger than baby boomers in other countries. Younger age and higher educational level are positively associated with digital technology adoption; however, little is known about Korean baby boomers' online activities and how their online activities are associated with social engagement and perceived social isolation. Methods. Data were obtained from 2012 Korean Baby Boomers Panel Study (n=3, 219). Negative binomial logistic regression was employed to examine factors associated with Korean baby boomers' online activities. Results. About 65% of Korean baby boomers at ages between 49 and 57 regularly went online for different purposes. Information search (50%) was the most common activity, followed by e-mailing (29%), and other online activities (i.e., listening to music, using social media, online banking, shopping, playing games), ranging from 22% to 17%. Korean baby boomers' internet use was positively associated with their face-to-face contacts with family (p < .05) and friends (p < .001), and formal social gatherings (p < .001) as well as perceived social isolation (p < .001). Discussion. Korean baby boomers in pre-retirement stage actively used internet for various purposes. The mixed outcomes regarding positive associations between Korean baby boomers' internet use and social engagement as well as feeling socially isolated give us the insights on psychosocial benefits and challenges associated with digital technology adoption. The complex relationships between objectively measured online and offline activities and self-evaluated social relationships will be further discussed.